S97. Clinical and electrophysiological characteristics of multiple myeloma eripheral neuropath: Aretrospective study in thirty-five patients. (May 2018) - Zhang, Wen Juan
Abstract : Introduction: To analyze the symptoms and signs in thirty-five multiple myeloma eripheral neuropath (MMPN) patients retrospectively. Characteristics of eleetrophysiological examinations were investigated. Methods: Thirty-five MM patients were reviewed and information gathered regarding clinicalcomplains neurological symptoms, and other concomitant disease. The records showed that nerve conduction velocity and skin sympathetic response and repetitive nelwestimulaljon(RNS) were performed in all patient. Needleelectromyography(EMG) and skin sympathetic response were also performed in all patients. Results: (1) The mean age of neurological clinical onset age was (60.23 ± 4.8) years old. The most common symptoms peripheral nerve system damage: sensory abnormalities (25 cases), the radicular pain (3 cases), dyskinesia (15 cases), the most common neurological signs reduced to lower extremity or distal upper extremity pain (18 cases), double knee jerk or ankle reflex to reduce or disappear (13 cases) and dry mouth or constipation or diarrhea patients or autonomic symptoms (20 cases); The first symptoms varied, such as dizziness, fatigue, increased foam in the urine, numbness of the limbs, back pain, etc. (2) Electrophysiological examination: there was no significant increase in high-frequency stimulation of ulnar nerve in all patients. Sensory nerve conduction velocity (SCV) abnormalities or motor nerve conduction velocity (MCV) abnormalities or SCV combined with MCV were found in 29 patients (83%). All patients underwent SSR and 17 (85%) abnormalities were detected. Conclusion: The most common peripheral nerve system impairment in MM is the sensation of "socks and gloves" distributed, paresthesia, paresthesia and numbness, severe movement disorders, autonomic nerve can also be involved. All the patients were no abnormal repetitive nerve stimulation, but abnormal electrophysiological system MM in patients with peripheral nerve abnormalities and autonomic nerve, suggesting that clinical manifestations may cause neurological or autonomic neuropathy mixed with. Electrophysiological examination of SSR can also be used for screening autonomic neuropathy in MMPN patients.